Mixed Signals: The Effect of Employment Training on Employment Outcomes for Previously Incarcerated Individuals - Nighswander, Tristan J. (International journal of offender therapy and comparative criminology, 2026)
This work investigates the effects of pre-employment training on employment outcomes for previously incarcerated individuals using two theories developed in the discipline of economics: human capital theory and signaling theory. Human capital theory suggests that preemployment training increases wages and the likelihood of employment by building relevant skills that would improve productivity. Signaling theory asserts that the completion of pre-employment training acts as a signal of participant ability, as ability is known to the applicant but unknown to employers. Using the National Longitudinal Survey of Youth, results support hypotheses related to signaling theory for individuals without a history of incarceration, but show no meaningful relationship between pre-employment training and employment outcomes for previously incarcerated individuals. Findings contribute to both economic and criminal justice theory and can be used to inform employment interventions for those with or without a history of incarceration.